2019
DOI: 10.1017/s1479244319000131
|View full text |Cite
|
Sign up to set email alerts
|

Women's International Thought and the New Professions, 1900–1940

Abstract: This article examines the “new professions” as alternative settings where women thought and wrote about the international. Presenting the case studies of Fannie Fern Andrews, Mary Parker Follett and Florence Wilson, it shows that, in emerging professional and disciplinary contexts that have hitherto lain beyond the purview of historians of international thought, these women developed their thinking about the international. The insights they derived from their practical work in schools, immigrant communities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…20 Taylor, cited in Owens and Rietzler 2021, 14. 21 Huber et al 2021;Hutchings and Owens 2021. 22 See, e.g.…”
Section: Expanding the History Of International Thoughtmentioning
confidence: 99%
“…20 Taylor, cited in Owens and Rietzler 2021, 14. 21 Huber et al 2021;Hutchings and Owens 2021. 22 See, e.g.…”
Section: Expanding the History Of International Thoughtmentioning
confidence: 99%
“…The interaction between intellectuals, public servants and policy-makers has also received the attention of historians, raising questions on the reception and impact of ideas in politics. Lawyers, civil servants and economists have signalled out as important links in connecting ideas to policies between the national and international spheres (Slobodian 2018;Wertheim 2020;Huber, Pietsch and Rietzler, 2019). Yet, as recent studies have shown, religious orders and their members were also significant contributors to developing and spreading ideas about world order (Moyn 2015;Erdmann 2005;Thompson 2015) What are the spatial boundaries of IPT?…”
Section: International Political Thoughtmentioning
confidence: 99%
“…More generally, very few works of international theory center on historical women (Owens, 2007;Hutchings 2009;Hansen, 2011;Kinsella 2014;Cochran 2017). This is mirrored in the small number of studies on the foundational role that women played in the field of international relations from the early twentieth-century (Sluga 2017;Stöckmann 2017;Owens, 2018;Huber, Pietsch, and Rietzler 2019;Owens and Rietzler 2021;Owens, Rietzler, Hutchings, Dunstan, 2021).…”
Section: The Gendered and Racialized Constitution Of Ir's Canonmentioning
confidence: 99%
“…More generally, very few works of international theory center on historical women (Cochran 2017;Hansen 2011;Hutchings 2009;Kinsella 2014;Owens 2007;Tickner and True 2018). This is mirrored in the small number of studies on the foundational role that women played in the field of IR from the early twentieth century (Huber, Pietsch, and Rietzler 2019;Owens 2018;Owens and Rietzler 2021;Owens et al Forthcoming;Sluga 2017;Stöckmann 2018).…”
Section: The Gendered and Racialized Constitution Of Ir's Canonmentioning
confidence: 99%